The effect of corporate social performance on firm financial performance: The moderating effect of ownership concentration - Harmer, N.L.; Pathiraja, P.M.D.S.; Priyadarshanie, W.A.N. (Faculty of Management Sciences, University of Sri Jayewardenepura, 2020)
Corporate Social Performance (CSP) is a relatively new area of study which refers to businesses’ relationship with people, organisations, communities and the earth. The main objective of the present study is to identify the impact of CSP on firm financial performance of listed companies on the Colombo Stock Exchange. The study investigated the moderating effect of ownership structure on the relationship above. Data were collected from 30 companies (Chemicals & Pharmaceuticals, Beverage Foods and Tobacco, Hotel and Manufacturing) for 2013-2018. Return on Equity and Return on Assets were used to measure firm financial performance. If firms invested in pollution control methods, it is considered they have satisfied corporate social performance. The sum of ownership percentage of the five largest investors was used to measure ownership concentration. Data were analysed employing regression analysis. Results revealed that there is a significant positive impact of CSP on financial performance of listed companies. Ownership concentration negatively moderates the relationship between CSP and a firm’s financial performance. Findings help policy makers and regulators better identify how ownership concentration is associated with firm incentives to engage in social performance, which leads towards better financial performance.
Keywords: Corporate social performance, firm financial performance, moderating effect, ownership concentration